2014
DOI: 10.1152/ajpcell.00398.2013
|View full text |Cite
|
Sign up to set email alerts
|

Acid-sensing ion channels are involved in epithelial Na+ uptake in the rainbow trout Oncorhynchus mykiss

Abstract: Dymowska AK, Schultz AG, Blair SD, Chamot D, Goss GG. Acidsensing ion channels are involved in epithelial Na ϩ uptake in the rainbow trout Oncorhynchus mykiss. Am J Physiol Cell Physiol 307: C255-C265, 2014. First published June 4, 2014 doi:10.1152/ajpcell.00398.2013.-A role for acid-sensing ion channels (ASICs) to serve as epithelial channels for Na ϩ uptake by the gill of freshwater rainbow trout was investigated. We found that the ASIC inhibitors 4=,6-diamidino-2-phenylindole and diminazene decreased Na ϩ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 51 publications
4
58
0
Order By: Relevance
“…the first bout of pH e recovery) can be attributed to the HCSW sturgeon having accumulated relatively more Na + than Cl − during this initial salt-loading period of the SW acclimation. The apparent association between pH e recovery and a relative increase of Na + accumulation during this time may be the result of inward Na + transport being tied to outward H + transport via an apical NHE or an apical H + -ATPase with associated Na + channel (Claiborne and Heisler, 1984;Iwama and Heisler, 1991;Dymowska et al, 2014), or the co-transport of Na + and HCO 3 − into the extracellular compartment via a basolateral Na + /HCO 3 − co-transporter (NBC1) (Hirata et al, 2003;Perry et al, 2003).…”
Section: Discussion Ncsw Acclimation In White Sturgeonmentioning
confidence: 99%
“…the first bout of pH e recovery) can be attributed to the HCSW sturgeon having accumulated relatively more Na + than Cl − during this initial salt-loading period of the SW acclimation. The apparent association between pH e recovery and a relative increase of Na + accumulation during this time may be the result of inward Na + transport being tied to outward H + transport via an apical NHE or an apical H + -ATPase with associated Na + channel (Claiborne and Heisler, 1984;Iwama and Heisler, 1991;Dymowska et al, 2014), or the co-transport of Na + and HCO 3 − into the extracellular compartment via a basolateral Na + /HCO 3 − co-transporter (NBC1) (Hirata et al, 2003;Perry et al, 2003).…”
Section: Discussion Ncsw Acclimation In White Sturgeonmentioning
confidence: 99%
“…Given that these blockers have been demonstrated to inhibit J Na,in in several studies, we cannot discount the role of H + -ATPase and a putative Na + channel in overall branchial J Na,in by CYA trout. Moreover, recent evidence has suggested that this putative Na + channel might be an acid-sensing ion channel (ASIC; Dymowska et al, 2014Dymowska et al, , 2015 that is DAPI-sensitive and not affected by phenamil.…”
Section: Series 3 -Effects Of Pharmacological Blockersmentioning
confidence: 99%
“…Based on the co-localization of Rhcg1 and NHEs (Fig. 4), PNA − ionocytes likely do not express apical Rhcg1 or Rhcg2 and might serve primarily for Na + /H + exchange via H + -ATPase and a putative Na + channel (Reid et al, 2003), which might be an ASIC (Dymowska et al, 2014). Finally, PVCs are likely important sites for J amm via Rhcg2, and H + -ATPase might be involved in active ammonia excretion by these cells (Nawata et al, 2007).…”
Section: Series 3 -Effects Of Pharmacological Blockersmentioning
confidence: 99%
See 1 more Smart Citation
“…the first bout of pH e recovery) can be attributed to the HCSW sturgeon having accumulated relatively more Na + than Cl − during this initial salt-loading period of the SW acclimation. The apparent association between pH e recovery and a relative increase of Na + accumulation during this time may be the result of inward Na + transport being tied to outward H + transport via an apical NHE or an apical H + -ATPase with associated Na + channel (Claiborne and Heisler, 1984;Iwama and Heisler, 1991;Dymowska et al, 2014), or the co-transport of Na + and HCO 3 − into the extracellular compartment via a basolateral Na + /HCO 3 − co-transporter (NBC1) (Hirata et al, 2003;Perry et al, 2003).Although a relative increase in Na + influx immediately following salinity exposure may have briefly aided in pH e recovery, such inward transport of Na + is counter-productive to the outward direction of Na + transport required for SW acclimation. As the sturgeon then made the physiological adjustments necessary to acclimate to SW and recover plasma osmolality ( presumably including a molecular reorganization of the gill epithelium in order to excrete Na + and Cl − ), this may have been to the detriment of any further pH e recovery.…”
mentioning
confidence: 99%